Rapid Urbanization and the Growing Water Risk Challenges in Ethiopia: The Need for Water Sensitive Thinking - Abraha, Tesfay; Tibebu, Assefa; Ephrem, Gebremariyam (Frontiers in Water, 2022)
Water connects all kinds of life like a thread. However, despite its indispensable roles, little attention has been paid to its effective management for generations. Water as a non-renewable natural resource, combined with a fast-growing urban population and climate change, has exposed countries to increasing water-related risks. Even though the water-related risk is becoming a fast-expanding worldwide concern, it is largely ignored and understudied in Ethiopia. As a result, this research aims to explore water-related risks at the country and basin levels, as well as to generate information on how water-related risks may influence current and future urbanization and urban settlement so that land use and water resource management planners can make better strategic decisions. To do this, the researchers employed a deductive exploratory (quantitative) research strategy that primarily centered on desk review and geographic analysis utilizing GIS and remote sensing. As a result, this study found that water availability per person per year is 1,109 m3, indicating that Ethiopia is experiencing water stress. According to the study, 41.6 % of Ethiopians live in basins receiving less than 500 m3 per capita each year. Furthermore, 178 urban centers (15%) are located in dry basins, 369 (33%) urban centers are located in low groundwater potential zones and 315 urban centers (28.15%) are located in an area with less than 100mm annual rainfall. In addition, 307 urban centers (28%) are all in high-drought-risk areas, while 307 urban centers (27%) are insignificant flood-prone areas. Overall, this study discovered that Ethiopia and its urban centers are experiencing water-related challenges. Hence, water-centric management strategies, such as water-smart community development, water-sensitive physical planning, water-smart technology, and a water-sensitive legal framework, are required to address the ongoing water risks.